Perilaku Pasca Kegagalan Layanan Dilihat dari Variabel Demografi dan Budaya - Kartika, Eka; Suprapti, Ni Wayan Sri; Rimbawan, I Nyoman Dayuh (E-Jurnal Manajemen, 2013)
This study is aimed to determine the customer behavior after a service failure seen from demographic and cultural characteristic of the customer of star hotels in the area of Badung. The data collected from 60 customers with individualist cultural background and 60 customers with collectivist cultural background. Chi-square test and cross tab analysis were used to process the data. Research revealed customers with high education, high income, and individualist cultural background are more likely to complaint to follow up a service failure. Collectivist customers with low education are tends to complaint via online media. Individualist customers are tends to complaint directly to the hotel manager. Collectivist customers tends to switch hotel when they faced a service failure. Cultural factor (not use to do complaint) is behind the decision of the collectivist customers whom not complaint. Individualist customers whom not complaint believed that complaint won’t solve the problem. Keywords: Post service failure behavior, collectivist culture, individualist culture.